Determination of Antibacterial Activity of Aucubigenin and Aucubin - Li1, Yang; Chen2, Lei; Han3, Guijun; Zhou3, Junhui; Zhao1, Ye (Asian Journal of Chemistry, 2014)
Because of the previously conflicted reports, the aucubigenin and aucubin have been reinvestigated for their antibacterial activities by a sensitive standardized micro-well dilution with automated spectrophotometric method, compared with paper disc diffusion method. The micro-well dilution assay was more accurate than paper disc diffusion method. The results showed that aucubin exhibited no antibacterial activity, while aucubigenin showed remarkable antibacterial activity against all of the tested bacteria. Aucubigenin was particularly more effective against Staphylococcus aureus with MIC value of 0.0313 mg/mL and MBC value of 0.0625 mg/mL, respectively.